Nanoemulsion stability: Experimental evaluation of the flocculation rate from turbidity measurements - Rahn-Chique, Kareem; Puertas, Antonio M.; Romero-Cano, Manuel S.; Rojas, Clara; Urbina-Villalba, German (Advances in colloid and interface science, 2012)
The coalescence of liquid drops induces a higher level of complexity compared to the classical studies about the aggregation of solid spheres. Yet, it is commonly believed that most findings on solid dispersions are directly applicable to liquid mixtures. Here, the state of the art in the evaluation of the flocculation rate of these two systems is reviewed. Special emphasis is made on the differences between suspensions and emulsions. In the case of suspensions, the stability ratio is commonly evaluated from the initial slope of the absorbance as a function of time under diffusive and reactive conditions. Puertas and de las Nieves (1997) developed a theoretical approach that allows the determination of the flocculation rate from the variation of the turbidity of a sample as a function of time. Here, suitable modifications of the experimental procedure and the referred theoretical approach are implemented in order to calculate the values of the stability ratio and the flocculation rate corresponding to a dodecane-in-water nanoemulsion stabilized with sodium dodecyl sulfate. Four analytical expressions of the turbidity are tested, basically differing in the optical cross section of the aggregates formed. The first two models consider the processes of: a) aggregation (as described by Smoluchowski) and b) the instantaneous coalescence upon flocculation. The other two models account for the simultaneous occurrence of flocculation and coalescence. The latter reproduce the temporal variation of the turbidity in all cases studied (380≤[NaCl]≤600mM), providing a method of appraisal of the flocculation rate in nanoemulsions. [Display omitted] ► Differences between the flocculation of solid particles and liquid drops are reviewed. ► The aggregation of an ionic nanoemulsion is studied following the change of its turbidity as a function of time. ► The behavior of the turbidity is reproduced using theoretical models. ► The influence of coalescence in the phenomenon of aggregation is appraised.